[OA238] Verification of field junctions in craniospinal proton radiotherapy. (August 2018) - Sadowski, Bartłomiej; Rydygier, Marzena; Komenda, Wiktor; Gajewski, Jan; Skowrońska, Katarzyna; Michalec, Barbara; Kopeć, Renata
Abstract : Introduction: Craniospinal irradiation (CSI) is a very important element in treating of medulloblastoma. Two laterally opposed cranial fields and several posterior spine fields are usually used for Proton Radiotherapy (PT) in medulloblastoma. In the case a potential dose inhomogeneity at the field junctions can appear. We propose the method of field junction verification based on ionization chambers array measurements and γ -index analysis. Materials and Methods: For field junction investigation, clinical plans for two anthropomorphic phantoms have been prepared. There were two opposed lateral brain fields and 2 posterior spine fields in the plan of 5-year-old child phantom. A plan for 10-year-old child phantom consisted of two opposed lateral brain fields and three posterior spine fields. Therefore we investigated two field junctions for 5-year-old child phantom and three field junctions for 10-year-old child phantom. We have chosen the same depth of isocenter for all fields. Dose distribution at the junctions were verified with ionization chambers array mounted in dedicated water phantom and centered in the overlap regions. Measured dose distributions were compared with planes exported from treatment planning system (TPS) by calculating γ -index: 3%/3 mm and 2%/2 mm. Each field junction was investigated at 5 different depths. Results: For 5-year-old child phantom we obtained better than 96% of measured points with γ -index ≤ 1 3%/3 mm criteria for all junctions. For 10-year-old child phantom we reached 99% for the same criterion. For both phantoms standard γ -index acceptance criteria of 2%/2 mm were above 87% for all junctions. Conclusions: The main benefit of PT of medulloblastoma is sparing of intermediate-to-low-dose to healthy tissues. This feature could translate into clinical reduction of side effects, including a lower risk for secondary cancers. However the crucial condition for a successful treatment is a careful and accurate field junction. We have proved that an ionization chamber array can be successfully used for field junction verification. The γ -index analysis of investigated junction areas shows that PT is a clinically acceptable method for medulloblastoma. The method we have developed can be widely used in proton therapy centers.